The Effect of Talenta Management, Knowledge Leader on Employee Performance and its Implications on Sustainable Competitive Advantage in Pt. Kimia Farma, Tbk - Sofia Fardhani; Cut Zurnali (Maneggio, 2024)
This study uses a quantitative approach, which aims to determine the influence of talent management, knowledge leader, employee performance toward a sustainable competitive advantage in PT. Kimia Farma Tbk Jakarta region business unit. This study was based on the existing theories are theories about the influence of talent management, knowledge leader, employee performance toward a sustainable competitive advantage. The sample data were obtained as many as 124 employees, the sample was drawn with a survey method as a primary data source. Data obtained directly from respondents using questionnaires. Data analysis included descriptive analysis, classic assumption test, simple linear regression analysis, multiple regression analysis, t test, F test and R² are processed using SPSS version 24. ???? = -0.775 + 0.178 X1 + 0.301 X2 + 0.220 Y1. 0.000 significance value <0.05 (α) and 45.148 F count> F table 2,68 showed positive results for all three variables. Value coefficient (R Square) shows the number of 0.530 which means a sustainable competitive advantage variables are influenced by variables Talent Management, variable knowledge leader, variable employee performance by 53% while the rest influenced by other variables that are not addressed in this study.